HUBUNGAN PARITAS, UMUR, DAN JENIS PERSALINAN DENGAN KEJADIAN PROLAPSUS UTERI DI RSUD DR.AHMAD MOCHTAR BUKITTINGGI TAHUN 2016 - Ahmalia, Renty; Melva, Lili (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
The cause of infant mortality in the world is due to pneumonia 20%, the remaining 22% is associated with malnutrition intake of breast milk. ASI is known as the main food for newborns that have colostrum which can provide natural immunity for babies. The number of morbidities is a reflection of the weakness of babies and toddlers. The baby's body will produce enough immunoglobulin on its own when it reaches around 4 months of age. The study was a quantitative type, using an analytical method, with a crossectional study design. The aim of the study was to determine the relationship between the level of knowledge and education of mothers with breastfeeding colostrum at the Posyandu in the Sikabu Community Health Center Working Area. The sample was 91 respondents with a total sampling technique. The results showed that there was a significant relationship between the level of knowledge of mothers with breastfeeding colostrum at the posyandu in the work area of Sikabu Health Center p-value = 0.006, there is a significant relationship between the education of mothers with breastfeeding colostrum at the posyandu in the work area of Sikabu Health Center p-value = 0.005. The level of knowledge of mothers about colostrum and maternal education at the Sikabu Community Health Center is mostly at a low level of knowledge and education. Sikabu Health Center is expected to be able to increase maternal knowledge, especially in the delivery of a variety of benefits that will be received by infants if given colostrum breast milk. Increasing the mother's knowledge can be done by distributing leaflets or posters at the posyandu in the Sikabu Community Health Center work area so that the mother can read the information while visiting the posyandu.